1995
DOI: 10.1007/bf03349830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4 weeks of octreotide treatment on prolactin, thyroid stimulating hormone and thyroid hormones in acromegalic patients. A double blind placebo-controlled cross-over study

Abstract: We aimed to test the hypothesis, that octreotide has a suppressive effect on unstimulated and TRH-stimulated PRL levels in both normo- and hyperprolactinaemic acromegalic patients, and besides to evaluate the effect of octreotide on unstimulated TSH and thyroid hormones. The present study is a doubleblind placebo-controlled cross-over trial; the 12 acromegalic patients were treated with octreotide or placebo (300 micrograms/d) for 4 weeks separated by a 12 weeks washout period. Before and after each 4 weeks pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…It has been suggested that mammosomatotroph cells comprise a significant portion of the cell population in pituitary adenomas from acromegalic patients (3 -6). We have previously reported that octreotide treatment for 4 weeks normalised PRL levels in patients with acromegaly and hyperprolactinaemia (7). In accordance with these results treatment with dopamine-D2 agonists suppressed GH secretion more efficiently in acromegalic patients with hyperprolactinaemia compared with those with normoprolactinaemia (8).…”
Section: Introductionsupporting
confidence: 79%
“…It has been suggested that mammosomatotroph cells comprise a significant portion of the cell population in pituitary adenomas from acromegalic patients (3 -6). We have previously reported that octreotide treatment for 4 weeks normalised PRL levels in patients with acromegaly and hyperprolactinaemia (7). In accordance with these results treatment with dopamine-D2 agonists suppressed GH secretion more efficiently in acromegalic patients with hyperprolactinaemia compared with those with normoprolactinaemia (8).…”
Section: Introductionsupporting
confidence: 79%
“…These findings may be due in part to increased clearance of FA1 in acromegaly (49,50). Nevertheless, FA1 levels did decrease in six of seven acromegalic patients, who had a significant reduction in GH levels during 4 weeks of octreotide therapy (51). This effect on FA1 levels may be due to a decrease in GH or IGF1 levels per se or to a direct effect of octreotide on FA1 secretion (48).…”
Section: Serum Igf1 Levelsmentioning
confidence: 84%
“…After screening the 1498 remaining articles for their title and abstract, the full text was evaluated for 37 studies. Of these, 10 RCTs [23][24][25][26][27][28][29][30][31][32] were included in the systematic review. All 10 studies composed the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Just 1 of the 10 RCTs specified that only surgery-naive patients could be enrolled [23]. Three of the studies used a crossover design [24,25,29]. The proportion of men and women was comparable in the studies and among the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%